The Enhancement of Students' Responsibility Attitude Through Role Model Method and Daily Assignments Based on Islamic Values in Elementary School - Putra, Dirgahayu; Zal'aidi, Muhammad; Syahendra, Syahendra; Sulastri, Sulastri; Pitrianti, Pitrianti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to improve students' sense of responsibility through the modeling method and daily assignments based on Islamic values at SD Islam Plus Daaruth Thullab 02 Koto Salak. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 25 fifth-grade students in the 2024/2025 academic year. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using descriptive quantitative methods. The results showed a significant improvement in students' sense of responsibility from the first to the second cycle, both in terms of the average questionnaire scores and the number of students who achieved the